Tools, models, and databases for making digital sequence information on genetic resources publicly available and accessible: A submission from CGIAR Genebank Accelerator - CGIAR Genebank Accelerator (2025)
This short submission from CGIAR is in response to the call for submissions issued by the CBD Secretariat through Notification 2024-115 (Ref.: SCBD/OES/DC/TS/CGA/KB/91971). CGIAR is developing tools and practices to promote sharing DSI in a transparent and accountable manner. Our observations and recommendations in this paper are based on our experiences and knowledge concerning the use of DSI in agricultural research and development, with a particular focus in this submission on conservation of crop genetic diversity and crop improvement.